The Influence of Workload and Organizational Culture on Employee Performance of Operational Division at Toyota (Auto 2000) Grand Depok City, Depok - Widodari, Sekar Ayu; Sudari, Suci Ayu; Rachmawati, Dwi (International Publisher, 2024)
This research aims to examine the influence of workload and organizational culture on employee performance of operational division. This research uses a quantitative method by distributing questionnaires to full time employees of sales and workshop divisions in Toyota (Auto 2000) Grand Depok City. The data is determined by probability sampling technique with convenience sample method as many as 56 respondents. The research sample is determined by analyzed using multiple linear regression data analysis methods with SPSS version 26 application software. The results of this study indicate that partially workload has a negative and significant effect on employee performance at Toyota (Auto 2000) Grand Depok City. Meanwhile, partially organizational culture has a positive and significant influence on employee performance. Workload and organizational culture simultaneously have a significant effect on employee performance with an Adjusted R Square value of 0.28 or 28%. In improving employee performance, companies can pay more attention to the targets that must be achieved indicators and increase the implementation of creativity & innovation also employee initiative.